Evidence for CP violation in B+→K∗(892)+π0 from a Dalitz plot analysis of B+→K0Sπ+π0 decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review, 2017)
We report a Dalitz plot analysis of charmless hadronic decays of charged B mesons to the final state K0Sπ+π0 using the full BABAR data set of 470.9±2.8  million B¯B events collected at the Υ(4S) resonance. We measure the overall branching fraction and CP asymmetry to be B(B+→K0π+π0)=(31.8±1.8±2.1+6.0−0.0)×10−6 and ACP(B+→K0π+π0)=0.07±0.05±0.03+0.02−0.03, where the uncertainties are statistical, systematic, and due to the signal model, respectively. This is the first measurement of the branching fraction for B+→K0π+π0. We find first evidence of a CP asymmetry in B+→K∗(892)+π0 decays: ACP(B+→K∗(892)+π0)=−0.52±0.14±0.04+0.04−0.02. The significance of this asymmetry, including systematic and model uncertainties, is 3.4 standard deviations. We also measure the branching fractions and CP asymmetries for three other intermediate decay modes.